ENGLISH LANGUAGE TEACHING (ESL): A PERSPECTIVE OF THE COMMON BASE OF THE BRAZILIAN CURRICULUM - Souza, Manuela Xavier Ribeiro de; Coutinho, Diógenes José Gusmão (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2024)
This article investigates the alignment of ESL teaching within the scope of the Brazilian Common Curricular Base (BNCC). With English proficiency becoming increasingly vital for academic, professional, and global communication purposes, BNCC emphasizes the importance of English language teaching in Brazil. Through a comprehensive examination of challenges, pedagogical strategies, and implications for policy and practice, this study aims to contribute to the discourse on improving English language teaching in Brazil. Drawing on literature, empirical research, and practical insights, the article provides practical recommendations for optimizing ESL teaching and learning in the Brazilian educational setting. By addressing the multifaceted dimensions of ESL teaching, the study offers guidance to stakeholders invested in improving English language proficiency among Brazilian students.